Grinding, Flotation and Drying Performance of the Clay- Containing Ores - Kashif, Nadia (Curtin University, 2024)
The thesis explores how clay minerals hinder mineral processing operations like grinding, drying, and flotation, with bentonite having a more severe impact than kaolin. It was found that addition of Ca2+ ions to bentonite-containing slurries mitigates these negative effects, particularly in grinding and flotation. Conversely, Ca2+ ions impaired the performance of kaolin-containing ores. The study underscores the importance of optimizing Ca2+ ion concentration in plant water for effective mineral processing of clay-containing ores.